Corium behavior and steam explosion risks: A review of experiments. (November 2018) - Shen, Pei; Zhou, Wenzhong; Cassiaut-Louis, Nathalie; Journeau, Christophe; Piluso, Pascal; Liao, Yehong
Highlights: Comprehensive review on experimental corium behavior and steam explosion risks. Small to intermediate scale experiments on premixing, triggering and propagation stages. Intermediate to large scale experiments using prototypic melt. OECD/SERENA2 project with KROTOS and TROI facilities. Observations and discussions provided on corium behavior and steam explosion risks. Abstract: After the Three Mile Island accident, numerous studies on the severe nuclear accident have been conducted. In a degraded core accident, the high-temperature melt corium may drop into the low-temperature coolant, which is called the fuel coolant interaction (FCI). Due to the velocity difference between the melt jet and the coolant as well as the violent film boiling around the melt, the melted corium may fragment into small particles. With the increase of the contact area between the melted corium and the coolant, plenty of coolant steam is produced. The timescale for heat transfer is shorter than that for pressure relief, resulting in the formation of shock waves and/or the production of missiles at a later time during the expansion of coolant steam explosion. During a severe reactor accident scenario, steam explosion is an important risk, even though its probability to occur is pretty low, since it could lead to large releases of radioactive material, and destroy the reactor vessel and surrounding structures. This study provides a comprehensive review of vapor explosion experiments, especially the most recent ones. In this review, small- to intermediate-scale experiments related to premixing, triggering and propagation stages are first reviewed and summarized in tables. Then intermediate- to large-scale experiments using prototypic melt are reviewed and summarized. The recent OECD/SERENA2 project including KROTOS and TROI facilities' work is also discussed. The studies on steam explosion are vital for reactor severe accident management and will lead to improved reactor safety.